Crustal structure of the Eastern Sierras Pampeanas of Argentina using high frequency local receiver functions - Perarnau, Marcelo Andres (2012)
The Eastern Sierras Pampeanas are basement cored outcrops uplifted in the Andean foreland where the easternmost segment of the Pampean flat slab segment starts dipping more steeply into the deeper mantle. These ranges of central Argentina known as the Sierras de Córdoba have an enriched-quartz composition and are bounded by a series of reverse faults. Different models have been suggested to represent the style of the thick-skinned deformation in this area. However the overall structure linking the exposed faults and terrane boundaries with their probable continuation at depth is unknown. In this paper we present images of the crustal structure beneath the Sierras de Córdoba using the common conversion point stacking method of high frequency local receiver functions recorded by the ESP broadband seismic array. The work consists of two transects located around 31°S and 32°S across the Sierras de Córdoba. The results show a consistent sharp Moho signal associated with a high contrast in seismic velocities in good agreement with the granitic character of the crust lying above the mafic upper mantle. The Moho morphology varies exhibiting thicknesses of 38. km in the west to 35. km in the east with a vertical shifting under the Sierra Chica. We relate this variable character to the presence of the boundary between the Pampia terrane and the Rio de La Plata craton. Our results for the intra-crustal structure indicate the presence of three discontinuities in the northern transect and at least two discontinuities in the southern transect. These discontinuities appear vertically displaced beneath the surface traces of the major range bounding faults providing evidence for the continuation to mid-crustal depths of the exposed reverse faults. Thus, the reverse faults seem to have displaced several horizontal intra-crustal interfaces. Finally in the lower crust we found a region which seems to be aseismic.